TARIFF ELIMINATION UNDER THE TRANS-PACIFIC PARTNERSHIP AND ITS IMPACT ON INDONESIA’S TRADE BALANCE - Pritish Kumar Sahu (Journal of Indonesian Economy and Business (JIEB), 2019)
Introduction: Indonesia has signed, and is in the process of signing, many bilateral and regional Free Trade Agreements (FTAs). Whether these trade agreements will benefit Indonesia on the economic front or not is still a matter for discussion. Background Problem: Signing TPP, raises many questions as to how this would affect the countries in Asian regions, including Indonesia. Novelty: Considering the criticism of CGE (Computer General Equilibrium) model, this paper uses the SMART simulation model, based on a partial equilibrium approach, to estimate the aggregate and commodity-level gains and losses for Indonesia with its partner countries during the post-tariff elimination period. Research Method: This study uses the World Bank’s World Integrated Trade Solution (WITS) Database. This database contains trade data for all the countries under a different nomenclature viz. at the two-digit, four-digit, and six-digit level. We use the HS-classified nomenclature at the six-digit level in order to estimate the impact of the removal of tariffs on Indonesia’s trade, i.e. both exports and imports. Findings: The finding reveals that if Indonesia does not take part in the Trans-Pacific Partnership Agreement, it will still have a trade surplus of $1.6 billion with the Trans-Pacific countries but joining the bloc would result in a trade deficit of $19 million. Joining the bloc would increase the imports from Japan, followed by the United States and Australia as against an increase in exports to the United States, followed by Malaysia and Vietnam. The post Trans-Pacific Partnership period will have many implications for Indonesia, it may face difficulties exporting to the member countries, even with an existing trade agreement, while in the long run the Trans-Pacific Partnership bloc could limit Indonesia’s trade prospects with these Pacific Rim countries and it may limit Indonesia influencing WTO outcomes. Conclusion: Trade agreements seem to have benefited Indonesia’s economy and its people in many ways over the years, even though it has an important cost for some people.